2012
DOI: 10.1136/oemed-2011-100578
|View full text |Cite
|
Sign up to set email alerts
|

10-Year prospective study of noise exposure and hearing damage among construction workers

Abstract: The study provides evidence of noise-induced damage at an average exposure level around the 85 dBA level. The predicted change in HTLs was somewhat higher than would be predicted by standard hearing loss models, after accounting for hearing loss at baseline. Limited evidence for an enhanced effect of high peak component noise was observed, and DPOAEs, although similarly affected, showed no advantage over standard hearing threshold evaluation in detecting effects of noise on the ear and hearing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
66
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 30 publications
1
66
0
5
Order By: Relevance
“…2,[12][13][14][15][16][17] Maintaining a fluid barrier at the surface of the sensory epithelium after damage is necessary to preserve the electro-chemical gradient that drives HC depolarization and therefore sensory transduction after the onset of hearing (reviewed in Wangemann). 18 Several major stressors cause HC death, [19][20][21][22] including aging, noise trauma, and exposure to therapeutic drugs with ototoxic side effects. When a HC is killed by noise or aminoglycoside antibiotics, surrounding SCs form a filamentous actin (F-actin) cable that constricts the HC at its apex.…”
mentioning
confidence: 99%
“…2,[12][13][14][15][16][17] Maintaining a fluid barrier at the surface of the sensory epithelium after damage is necessary to preserve the electro-chemical gradient that drives HC depolarization and therefore sensory transduction after the onset of hearing (reviewed in Wangemann). 18 Several major stressors cause HC death, [19][20][21][22] including aging, noise trauma, and exposure to therapeutic drugs with ototoxic side effects. When a HC is killed by noise or aminoglycoside antibiotics, surrounding SCs form a filamentous actin (F-actin) cable that constricts the HC at its apex.…”
mentioning
confidence: 99%
“…The adverse relationship between NIHL and work experience in this study can be considered an important fac- tor for hearing loss, as indicated by other investigators (33)(34)(35)(36). Years of active work was considered as the basic measure for the chronic status of noise exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Years of active work was considered as the basic measure for the chronic status of noise exposure. In this regard, calculation of daily hours of active work constitutes another measurement method, which is by itself more detailed (36). Since the auditory effect of noise is gradual, estimating the exposure time by only measuring the working hours is not adequate; therefore, use of a larger time frame, similar to the one applied in the present study, is often needed.…”
Section: Discussionmentioning
confidence: 99%
“…However, mechanized construction is noisy, with the most powerful equipment often being the loudest [9]. Hand-held electrical equipment is versatile and precise; there is a diverse range of such tools, and they are often inexpensive.…”
Section: Introductionmentioning
confidence: 99%